Different clinical characteristics in sporadic young-age onset colorectal cancer. Issue 37 (September 2016) - Lee, Jieun; Kim, In-Ho; Kim, Jin Su; Kim, Sang Woo; Kim, Jun Gi; Oh, Seung Tack; Kang, Won Kyung; Lee, Myung Ah
Abstract : Abstract: The incidence of colorectal cancer (CRC) is increasing in young-age patients, but the clinical history is not established. Authors analyzed the clinical characteristics of young-age onset CRC to support basic information for setting treatment policies. Between January 2006 to January 2014, 100 CRC patients diagnosed at the age of 10 to 39 were analyzed. The clinicopathologic characteristics were reviewed based on medical records. Survival outcomes including overall survival (OS), disease-free survival (DFS), and progression-free survival (PFS) were analyzed. This study was conducted as a retrospective, observation study. Among 100 patients, 86 patients were diagnosed as CRC at their thirties. Seventy-nine patients had no familial history of cancer. At initial diagnosis, 59 patients showed the normal CEA level (⩽3 ng/mL), and 61 patients were diagnosed as advanced CRC (40% stage III, 21% stage IV). Sixty-four patients had lower location-sigmoid colon, rectosigmoid junction, or rectum. Recurrence rate was 7.9% in stage I to III CRC. Although median OS was not reached, patients with normal CEA level showed better survival outcome ( P = 0.013) and patients with perineural invasion showed poorer survival ( P = 0.011). The 5-year survival rate of total patient population was estimated as 75%. However, median OS of stage IV patients were 19 months (range 7.9–60.63 months), shorter than historical data of >24 months. Young-age CRC was most commonly diagnosed at their thirties, with no familial history, normal range of CEA and located below sigmoid colon. In young-age onset stage IV CRC, patients showed inferior OS compared to historical data. Based on our data, different surveillance program other than serum CEA level (e.g., sigmoidoscopy) is needed in young-age patient population.